Props Design on Manual Assembly Lines in Industrial Engineering Design Practicum 3 With Learning Factory Approach - Ahmad Syarif Yumna Najmudin; Lobes Herdiman; W.A. Jauhari (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Industry requires educational institutions as providers of labor to continue to optimize the learning process on material that is in harmony with existing cases in the industrial world. The Industrial Engineering Study Program of Sebelas Maret University Surakarta (PSTI-UNS) has sought these demands by implementing integrated practice learning with the learning factory concept approach. Identification of design needs was obtained after observations and evaluations of the learning process on PTI Practicum 3. This study contains requirements in designing tools to accommodate lab work in linear PTI Practicum manuals. The tools needed include storage, hand trolleys, storage racks, and work stations. The selection of the work station concept was carried out with Focus Group Discussion (FGD) with specified selection criteria. The criteria for selecting a tool for practicum facilities include the suitability of learning objectives, material